Doppler radar-derived wind field of five tornado events with application to engineering simulations. (1st October 2017) - Refan, Maryam; Hangan, Horia; Wurman, Joshua; Kosiba, Karen
Highlights: Made a first attempt to generate a preliminary tornado wind field database. Analyzed single-Doppler radar data of five tornado events. Determined tangential velocity profile, swirl ratio and vortex structure of field tornadoes. Created a preliminary yet detailed wind field database that is greatly beneficial to tornado simulations. Field vortex structure variation with tangential velocity matches laboratory results. Abstract: Doppler radar data corresponding to five tornado events are analyzed using the Ground-Based Velocity Track Display method and the three-dimensional velocity field of nine volumetric samples is extracted. These samples are selected to cover a range of wind speeds (between 36 m/s and 64 m/s) and vortex structures representative of EF0 to EF3 tornadoes in a first attempt to generate a tornado wind field database. Tangential velocity profiles, swirl ratios and vortex structures, i.e. single-celled or two-celled vortex, are determined for each of these volumetric samples. Among the nine volumetric samples, two show single-celled characteristics, vortex breakdown bubble is evident in one and four demonstrate two-celled vortex characteristics. The radial profiles of the tangential velocity are in good agreement with a modified Rankine vortex model. The variation of maximum tangential velocities with height is very different when compared to the velocity variation in typical atmospheric boundary layer flows. The swirl ratios of the tornado volumetric samples are computed using the flow rate through the updrafts and the maximum circulation in the flows.